Deep oncopanel sequencing reveals within block position-dependent quality degradation in FFPE processed samples - Zhang, Yifan; Blomquist, Thomas M; Kusko, Rebecca; Stetson, Daniel; Zhang, Zhihong; Yin, Lihui; Sebra, Robert; Gong, Binsheng; Lococo, Jennifer S; Mittal, Vinay K; Novoradovskaya, Natalia; Yeo, Ji-Youn; et al. (Genome biology, 2022)
BACKGROUND: Clinical laboratories routinely use formalin-fixed paraffin-embedded (FFPE) tissue or cell block cytology samples in oncology panel sequencing to identify mutations that can predict patient response to targeted therapy. To understand the technical error due to FFPE processing, a robustly characterized diploid cell line was used to create FFPE samples with four different pre-tissue processing formalin fixation times. A total of 96 FFPE sections were then distributed to different laboratories for targeted sequencing analysis by four oncopanels, and variants resulting from technical error were identified. RESULTS: Tissue sections that fail more frequently show low cellularity, lower than recommended library preparation DNA input, or target sequencing depth. Importantly, sections from block surfaces are more likely to show FFPE-specific errors, akin to "edge effects" seen in histology, while the inner samples display no quality degradation related to fixation time. CONCLUSIONS: To assure reliable results, we recommend avoiding the block surface portion and restricting mutation detection to genomic regions of high confidence.
Keywords: fixace tkání; High-Throughput Nucleotide Sequencing; formaldehyd; zalévání tkání do parafínu; Formaldehyde; lidé; Sequence Analysis, DNA; Paraffin Embedding; Cancer genomics; FFPE; Humans; Next-generation sequencing; sekvenční analýza DNA; Oncopanel sequencing; vysoce účinné nukleotidové sekvenování; Precision medicine; Tissue Fixation; Preanalytics